Paternal involvement in educational activities and its influence on academic achievement - Mariano, Kachela Albert (2009)
This study was conducted to see how involved fathers are in their children's educational activities and the relationship of paternal involvement and academic achievement. Research constructed questionnaires (the Paternal Involvement Scale and the Sources of Paternal Involvement Scale) were administered to a sample of above average and below average grade students. Interviews were conducted for verification of data. It was found that most children receive help from their mothers, siblings, househelps, or grandparents. Fathers have high involvement in the responsibility domain. Competence wss the only source of paternal involvement that yielded a significant relationship in both above and below average categories. Increasing the fathers' competence may prove to be beneficial even to fathers of highly achieving children.